2001
DOI: 10.1002/ajmg.1365
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an association with the serotonin transporter promoter region polymorphism and autism

Abstract: We have examined three functional polymorphisms, serotonin transporter promoter region polymorphism (5-HTTLPR), dopamine D4 exon III repeat region (DRD4), and catechol-O-methyltransferase (COMT), in a small family-based design toward identifying candidate genes that confer risk for autism. A significant excess of the long/long 5-HTTLPR genotype was observed (likelihood ratio = 7.18; P = 0.027; 2 df; n = 33 families) as well as preferential transmission of the long allele of the 5-HTTLPR (TDT chi-square = 5.44;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(88 citation statements)
references
References 55 publications
(42 reference statements)
1
85
0
2
Order By: Relevance
“…64 However, studies probing associations of 5-HTTLPR with autism reached conflicting results. [65][66][67][68] The serotonin system is quite diffuse, affecting many different physiological mechanisms, and it may be difficult to assume a pathophysiological pathway specific for autism-spectrum disorders. There are many other genes in this system, and most have not been probed for an association with autism-spectrum disorders.…”
Section: Discussionmentioning
confidence: 99%
“…64 However, studies probing associations of 5-HTTLPR with autism reached conflicting results. [65][66][67][68] The serotonin system is quite diffuse, affecting many different physiological mechanisms, and it may be difficult to assume a pathophysiological pathway specific for autism-spectrum disorders. There are many other genes in this system, and most have not been probed for an association with autism-spectrum disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found an association of the short alleles of 5HTTLPR with AD, 217,[230][231][232][233] fewer studies of the long alleles. 234,235 Some studies did not replicate these findings. 214,[236][237][238][239][240][241][242][243] Three studies have assessed the effects of the 5HTTLPR on whole-blood serotonin (5-HT) or platelet 5-HT parameters in AD.…”
Section: Chromosome 17mentioning
confidence: 99%
“…This characteristic was shown to aggregate in families, [7][8][9][10][11] and suggests that an abnormality in the serotonin (5-HT) system may be involved in autism etiology. Additional lines of evidence, largely implicating the serotonin transporter (5-HTT) in the regulation of 5-HT levels, further support this hypothesis: (1) selective 5-HT reuptake inhibitors (SSRIs) improve some of the autistic symptoms, such as ritualistic behavior and aggression, through blockage of 5-HTT and consequent increase in synaptic levels of 5-HT; 12,13 (2) specific alleles at an insertion/ deletion promoter polymorphism (5-HTT gene-linked polymorphic region, HTTLPR) regulate the transcription of the 5-HT transporter gene (SLC6A4) and the activity of 5-HTT in human platelets and in lymphoblastoid cells, the long allele (L) being responsible for increased transcriptional efficiency and higher rate of 5-HT uptake by the 5-HTT; [14][15][16] (3) association with autism of both the L and the short (S) alleles at the HTTLPR polymorphism has been reported; [17][18][19][20] (4) another polymorphism, a variable number of tandem repeats (VNTR) in intron 2 (Serotonin transporter intron 2, Stin2), has been described in the SLC6A4 gene in humans and mice, and acts as a transcriptional enhancer in the mouse embryo. 21,22 Given these observations, it is quite plausible that specific functional variants of the 5-HT transporter gene, associated with high 5-HT uptake rates, determine whether 5-HT levels are increased inside cells, and that such specific variants play a role in the occurrence of hyperserotonemia in a subset of autistic patients.…”
mentioning
confidence: 99%